Land Contour Analysis for the Planning of Al-Amin Living Lab and Industrial Park in Sampe Cita Village, Kutalimbaru District - Harindra Syam, Fariz; Wisdianti, Dara; Dwi Ardianti, Syahna (Action Research Literate, 2025)
Land contour measurement is a fundamental step in the process of planning and designing areas, especially in integrated areas based on education, innovation, and eco-education tourism. This study aims to determine the topography of the Al-Amin Living Lab and Glugur Rimbun Industrial Park in Sampe Cita Village, Kutalimbaru District, as a base map for area design. The study used a descriptive-quantitative approach with geodetic GPS-based contour measurement techniques and a 20-meter grid method. The elevation data obtained was processed using Global Mapper software to produce a topographic map with a contour interval of 0.5 meters. The results of the study show that around 60% or ±12 hectares of the total land has relatively flat contours, especially in the west and south, while the other 40% or ±8 hectares has steep and ravine-like contours, predominantly in the east and north near the river. Land slope analysis confirmed these topographical variations and became an important basis for determining zoning, building placement, circulation routes, and land engineering strategies in the area design. This study produced the precision topographic maps needed for the master plan of the Al-Amin Living Lab and Industrial Park and supported the development of an area oriented towards sustainability and the integration of educational, economic, and environmental functions.